2018
DOI: 10.31850/jgt.v7i1.321
|View full text |Cite
|
Sign up to set email alerts
|

Respon Pemberian Berbagai Dosis Pupuk Organik Cair Terhadap Pertumbuhan Dan Perkembangan Cabai Merah

Abstract: Masalah yang dihadapi dalam pengembangan tanaman cabai adalah tingginya penggunaan pupuk anorganik di tingkat petani. Hal ini mendorong dilakukan penelitian yang menggunakan pupuk organik. Penelitian ini Bertujuan untuk menganalisis respon tanaman cabai merah pada penggunaan pupuk organik cair. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK), yang terdiri dari lima perlakuan yaitu pemberian pupuk organik cair masing-masing 50 ml, 60 ml, 70 ml, 80 ml, 90 ml per liter air dan kontrol yang diulang masing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…The advantage of LOF is increasing nutrient absorption effectiveness, easier to absorb, improves the quality of plant products, and reduces inorganic fertilizer [4]. The application of liquid organic fertilizers can also increase the growth and yield of red chili [5].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of LOF is increasing nutrient absorption effectiveness, easier to absorb, improves the quality of plant products, and reduces inorganic fertilizer [4]. The application of liquid organic fertilizers can also increase the growth and yield of red chili [5].…”
Section: Introductionmentioning
confidence: 99%
“…The growth yield in the form of photosynthate accumulation will increase which causes nutrient uptake to increase as well, and vice versa. A study [37] revealed that liquid organic manure has significantly affected the seedling growth of Anthocephalus macrophyllus by the increase of plant height, diameter and leaf number as well as fresh and dry weight/biomass, as well as can increase plant growth and yield on the other annual crops such as Red Chilli/Capsicum annum [38] and corn [39] .…”
Section: The Biomass Of Arrowroot and Cardamommentioning
confidence: 99%
“…POC fertilizer application for red chili plantations is carried out by contract farmers with a dose of 80 ml per liter of water so that the red chili crop contract farmers experience optimal growth. The fertilizer dosage given by farmers is by research conducted by Makmur & Magfirah (2018), that the growth of red chilies will be optimal in administering 50 ml and 80 ml POC fertilizer doses per liter of water.…”
Section: Comparison Cultivation Practice Of Contract Farming Farmers ...mentioning
confidence: 99%